Changes in Vitamin E and β-Carotene Contents in Various Edible Cassava Leaves (Manihot esculenta Crantz) of Different Ages across Multiple Seasons - Alphonse Laya; Benoît B. Koubala (International Journal of Agronomy)
Vitamin E and carotenoids belong to a group of bioactive compounds that have an important effect on human health. The present study aims to investigate for the first time the concentration of vitamin E, α-, γ-, and δ-tocopherol, and β-carotene in edible cassava leaves during different ages. The analysis was performed using colorimetry and high-performance liquid chromatograph (HPLC) methods. A significant difference was found among α-, γ-, and δ-tocopherol concentrations in leaves; γ- and α-tocopherol isomer contents were the predominant in amount, respectively. Among the leaves, AD variety harvested at 6 months after planting (MAP) was the highest in total vitamin E (222 μgα-TE/g). However, the highest γ-tocopherol content (2782 μg/100g) and the content of biologically active vitamin E (1244 μg/100g) were found in EN variety at 6MAP, whereas the highest value (42 μg/g) of β-carotene was found in AD variety at 12MAP. Total vitamin E and tocopherol isomers composition varied among varieties and seasons as did β-carotene. The effects of varieties and harvest ages on the biosynthesis regulation of these compounds were confirmed by principal component analysis (F1x F2: 74.34%). Edible cassava leaves can be considered as sources of vitamin E for natural dietary antioxidant during different ages, and the best time to harvest EN and AD varieties is at 6MAP on the basis of α-tocopherol equivalent or content of biologically active vitamin E content, and EN and AD varieties performed the overall best. Thus, the edible cassava leaves are among the leafy vegetables that could be helpful to suggest as a part of daily meal for health benefits and pharmaceutical purposes.